A method for improving the long-term solidification effect of fly ash cement solidified body

By hydrothermal treatment of fly ash and adding fiber and polymer modified asphalt, the problems of fly ash cement cured body aging and heavy metal leaching are solved, achieving higher stability and mechanical strength.

CN119158864BActive Publication Date: 2025-04-15GUANGDONG YINGKE WATERPROOF REINFORCEMENT TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411248034.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2025-04-15
Estimated Expiration
2044-09-06

AI Technical Summary

Technical Problem

The existing fly ash cement cured bodies are prone to aging during long-term use, resulting in heavy metal leaching from the cured bodies, polluting the environment, and insufficient curing effect.

Method used

By hydrothermal treatment of fly ash, sodium silicate is generated to reduce the solubility of heavy metals, and synthetic fibers or metal fibers are added to enhance the mechanical properties of the cured body. At the same time, polymer modified asphalt is used to coat the cement cured body to improve its resistance to carbonation and waterproof properties.

Benefits of technology

It significantly improves the long-term stability and anti-aging properties of fly ash cement cured bodies, reduces the risk of leaching of heavy metals, and enhances the mechanical strength and durability of the cured bodies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005031418490000191
    Figure BDA0005031418490000191
  • Figure BDA0005031418490000201
    Figure BDA0005031418490000201
  • Figure BDA0005031418490000211
    Figure BDA0005031418490000211
Patent Text Reader

Abstract

The invention discloses a method for improving the long-term solidification effect of fly ash cement solidified body, which belongs to the technical field of fly ash solidification, and the method comprises the following steps: S1, collecting fly ash from the incineration of domestic waste, and first subjecting the fly ash from the incineration of domestic waste to hydrothermal treatment to form a uniform slurry; S2, adjusting the viscosity of the slurry, gradually adding synthetic fiber or metal fiber to the slurry with adjusted viscosity, and obtaining a slurry containing synthetic fiber or metal fiber; S3, after pouring and condensing, obtaining a cement solidified body, and crushing the cement solidified body with a jaw crusher; heating the polymer modified asphalt and the matrix asphalt to 160°C-185°C respectively, and maintaining them in the temperature range to obtain an asphalt-coated cement solidified body. The present invention can improve the anti-carbonation performance of the fly ash cement solidified body, prevent the aging of the fly ash cement solidified body, improve the long-term stability of the fly ash cement solidified body, and improve the long-term solidification effect of the fly ash cement solidified body.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fly ash solidification, and in particular to a method for improving the long-term solidification effect of a fly ash cement solidification body. Background Art

[0002] Fly ash from the incineration of municipal solid waste (hereinafter referred to as "fly ash") contains a variety of heavy metal substances such as Cd, Cr, Cu, Pb, Hg, Ni and dioxin pollutants, and the amount produced is huge. When fly ash is disposed, it may pollute groundwater. It is one of the key and difficult points of hazardous waste management in my country. Fly ash also contains salt and chloride. The chloride in fly ash mainly includes two forms: water-soluble chloride and water-insoluble chloride. Water-soluble chlorides mainly include sodium chloride (NaCl), potassium chloride (KCl), calcium chloride (CaCl 2 ) and calcium chloride hydroxide (CaClOH), which are mainly derived from biomass components and food waste in the incineration of waste, as well as intermediate products of flue gas dehydrochlorination. The water-insoluble chlorides mainly include Friedel's salt (3CaO·Al 2 O 3 ·CaCl 2 10H 2 O), AlOCl, etc., which are mainly formed under high temperature conditions of garbage incineration. The current mainstream treatment method is "blocking", that is, chelating and solidifying fly ash before landfilling - after adding cement or chelating agent to fly ash, it is sent to landfill after its properties are more stable by physical or chemical means. As the solidification and stabilization process proceeds, heavy metals may transform from metastable state to stable state, which is usually related to the chemical action of the solidifying agent (such as cement or chelating agent). Although the heavy metals in the stable state are not easy to be leached, the initial solidified body has a good heavy metal fixation effect, but because the fixation effect of fly ash is not sufficient, the fly ash solidified body is easily affected by the environment in the landfill, and the long-term effect of fly ash fixation needs to be improved. Specifically, the characteristics of chelating agent fly ash solidification are as follows: Although the volume increase of fly ash stabilized by inorganic agents is small, the heavy metals in the solidified body are easily dissolved under acidic conditions, causing harm to the environment, and cannot meet the safety requirements of long-term stability of hazardous waste. Although organic agents are more stable in fixing fly ash, with less addition and better solidification effect than inorganic agents, they are more expensive than inorganic agents. Due to the complex chemical composition of fly ash and the unstable existence of heavy metals in it, inorganic agents and organic agents have different selectivity for heavy metals, making it difficult to stabilize and fix all heavy metals, and the fixation effect is insufficient. Therefore, to a certain extent, its application in the treatment of fly ash from the incineration of domestic waste is restricted.

[0003] However, compared with the chelating stabilization system, the heavy metal fixation in the cement solidification system is more stable. Studies have shown that the fixation effect of the cement solidification system on heavy metals may decay due to the aging of the solidification stabilization system. In the early stage of aging, the leaching of heavy metals may be relatively low, but over time, if cracks appear in the solidified body, it may provide a channel for the migration of heavy metals. In a slightly acidic environment, the concentration of hydrogen ions in the solution increases, which may reduce the precipitation solubility of heavy metals in the cement solidified body, making it easier for heavy metals to exist in ionic form and leaching heavy metals from the cement solidified body. In addition, since the waste incineration fly ash contains a high content of chloride ions, chloride ions can form stable complexes with a variety of heavy metal ions in the fly ash. The solubility of these complexes is usually higher than that of the corresponding metal hydroxides or metal oxides, thus increasing the concentration of heavy metal ions in the leaching solution and increasing the problem of heavy metal ion leaching after the cement solidified body ages. The cumulative effect may cause the concentration of heavy metals on the surface or near-surface area of ​​the cement solidified body to increase, eventually exceeding the limit. If there are problems with the landfill's impermeable layer or it is poorly managed, heavy metals in fly ash may still enter the environment through leakage and other means.

[0004] Fly ash asphalt curing uses asphalt materials as curing agents, which are evenly mixed with fly ash at a certain temperature to produce a saponification reaction, so that harmful substances are contained in the asphalt to form a solid body, thereby being stabilized. Since asphalt is a hydrophobic substance, the complete asphalt solid body has excellent waterproof properties. Asphalt also has good adhesion and chemical stability, and has high corrosion resistance to most acids and alkalis. Summary of the invention

[0005] In order to overcome the shortcomings of the prior art, the purpose of the present invention is to provide a method for improving the long-term solidification effect of fly ash cement solidified body, which method can improve the anti-carbonation performance of the fly ash cement solidified body, prevent the aging of the fly ash cement solidified body, and the appearance of cracks on the surface of the solidified body, reduce the risk of heavy metal leaching in the fly ash cement solidified body caused by the increase of salt and chloride ions in the fly ash, improve the long-term stability of the fly ash cement solidified body, and improve the long-term solidification effect of the fly ash cement solidified body.

[0006] The purpose of the present invention is achieved by the following technical solutions:

[0007] A method for improving the long-term solidification effect of fly ash by a fly ash cement solidification body comprises the following steps:

[0008] S1. Collect fly ash from incineration of domestic waste, place the fly ash in a hydrothermal reactor for hydrothermal treatment, and after the hydrothermal treatment, collect chlorine generated by decomposition of fly ash chloride during the hydrothermal treatment through a closed pipeline system connected to the hydrothermal reactor. After the chlorine is collected, put the hydrothermal treatment product in the hydrothermal reactor into a stirring device, put cement into the stirring device for stirring, and stir the added water evenly to form a uniform slurry;

[0009] S2, selecting synthetic fibers or metal fibers of appropriate length, adjusting the viscosity of the slurry so that the synthetic fibers or metal fibers are evenly dispersed in the slurry, gradually adding the synthetic fibers or metal fibers to the slurry with adjusted viscosity, first stirring at a low speed to start mixing to avoid damaging the synthetic fibers or metal fibers, and gradually increasing the stirring speed so that the synthetic fibers or metal fibers are evenly dispersed in the slurry, thereby obtaining a slurry containing synthetic fibers or metal fibers;

[0010] S3. After pouring and solidifying the slurry containing synthetic fibers or metal fibers, a cement solidified body is obtained, and the cement solidified body is crushed by a jaw crusher, and the crushed cement solidified body is put into an asphalt concrete mixing device; the polymer modified asphalt and the base asphalt are heated to 160°C-185°C respectively, and maintained in this temperature range, and the heated polymer modified asphalt is added to the asphalt concrete mixing device and stirred evenly so that the surface of the crushed cement solidified body is provided with a layer of the polymer modified asphalt, and cooled and solidified to form a polymer modified asphalt layer on the surface of the crushed cement solidified body. After the polymer modified asphalt layer is formed, the cooled and solidified polymer modified asphalt layer is heated by a heating device of the asphalt concrete mixing device to soften the cooled and solidified polymer modified asphalt layer so that the crushed cement solidified body can be separated, and the heated base asphalt is continuously added to the asphalt concrete mixing device, and the separated crushed cement solidified body and the heated base asphalt are stirred evenly, and after cooling and solidification, a base asphalt layer is formed on the polymer modified asphalt layer to obtain an asphalt-coated cement solidified body.

[0011] Furthermore, in step S2, a forced mixer is used to stir the synthetic fibers or metal fibers.

[0012] Furthermore, in step S1, in the stirring device, the weight ratio of the fly ash, the cement and the water added is 1:0.2:3.

[0013] Furthermore, in step S2, the synthetic fiber is one of polyester fiber, polyamide fiber, polyacrylonitrile fiber, polyvinyl formal fiber, polyvinyl chloride fiber, and polyurethane elastic fiber; the metal fiber is one of stainless steel fiber, copper fiber, nickel fiber, and aluminum fiber.

[0014] Furthermore, in step S1, the cement is sulphoaluminate cement.

[0015] Furthermore, in step S3, the jaw crusher is one of a simple swing jaw crusher, a compound swing jaw crusher or a hydraulic jaw crusher.

[0016] Furthermore, the jaw crusher is one of a simple swing jaw crusher, a compound swing jaw crusher or a hydraulic jaw crusher.

[0017] Furthermore, in step S3, the polymer modified asphalt is obtained by modifying the base asphalt with one of the following polymers: SBS (styrene-butadiene-styrene block copolymer), SBR (styrene-butadiene rubber), EVA (ethylene-vinyl acetate copolymer), PE (polyethylene), and polyurethane (PU).

[0018] Furthermore, in step S1, the cement is put into the stirring device for stirring, and the added water is stirred evenly. In this step, sodium tetraphenylborate is also added and stirred evenly.

[0019] Furthermore, after obtaining the asphalt-coated cement solid body in step S3, the insoluble phosphate salt and biochar are mixed, and the mixture of the insoluble phosphate salt and the biochar is buried in the surface layer of the soil of the domestic waste landfill, and the phosphate-solubilizing bacteria microbial preparation is applied to the soil of the domestic waste landfill, and then the asphalt-coated cement solid body is buried in the domestic waste landfill.

[0020] Furthermore, the sparingly soluble phosphate is at least Ca(H 2 PO 4 ) 2 , Ca(H 2 PO 4 ) 2 ·CaHPO 4 , Ca 10 (PO 4 ) 6 (OH) 2 One of them.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The present invention provides a method for improving the long-term solidification effect of fly ash cement solidification body. After the fly ash is hydrothermally treated, the silicon dioxide (SiO 2 ) and sodium oxide (Na 2 O) reacts with water to form sodium silicate (Na 2 SiO 3 ), sodium silicate will undergo hydrolysis reaction to generate silicic acid and sodium hydroxide, which will reduce the solubility of sodium silicate in water and acid. After the chlorine gas generated by the decomposition of fly ash chloride during the hydrothermal treatment is collected, the chloride ion content in the subsequent fly ash cement solidification body is reduced, and the heavy metals brought by chloride ions are more easily leached from the cement solidification body. At the same time, sodium silicate is a strong base weak acid salt, which can react with heavy metal ions (such as Pb 2+ 、Cd 2+ Cr 3+ The heavy metal silicate is usually reacted with the fly ash cement (such as sodium silicate) to generate heavy metal silicate. The heavy metal silicate usually has a low solubility and is therefore not easily dissolved in an aqueous solution, showing good chemical stability. The generation of sodium silicate also reduces the solubility of sodium ions in water and acid, reduces the hygroscopicity of sodium salts in cement solidification, avoids the generation of cracks and damage to the fly ash cement solidification body, and can improve its durability. When the cement is put into the stirring device for stirring, sodium tetraphenylborate is added. Sodium tetraphenylborate can be partially soluble in water and will dissociate into tetraphenylborate ions. and sodium ions (Na + ), tetraphenylborate ions and potassium ions undergo ion exchange reaction to form potassium tetraphenylborate (KB(C 6 H 5 ) 4 ) and sodium ions. Potassium tetraphenylborate is a water-insoluble compound, so it will stabilize in the fly ash cement solid body in the form of precipitation, which also reduces the hygroscopicity of potassium ions in the cement solid body, avoids the generation of cracks and damage in the fly ash cement solid body, and can improve its durability; the matrix asphalt has good hydrophobicity, which makes the asphalt solid body resist water penetration and reduces the erosion of water on the fly ash cement solid body. Since water is CO 2 carrier, indirectly reducing CO 2 The permeability of fly ash cement can improve the anti-carbonation performance of fly ash cement solidification, resist external factors that affect cement aging, and prevent the aging of fly ash cement solidification; the adhesion of asphalt can help fix chloride ions and reduce the migration and leaching of chloride ions in fly ash from cement solidification. The above effects solve the problem of heavy metal ion leaching after cement solidification after aging. In addition, compared with fly ash asphalt solidification, the mechanical strength of cement solidification coated with asphalt is higher.

[0023] After obtaining the asphalt-coated cement solidified body, the insoluble phosphate salt and biochar are mixed, and the mixture of the insoluble phosphate salt and the biochar is buried in the surface layer of the soil of the domestic waste landfill, and the phosphate-solubilizing bacteria microbial preparation is applied to the soil of the domestic waste landfill, and then the asphalt-coated cement solidified body is buried in the domestic waste landfill. The activity of phosphate-solubilizing bacteria is highest under slightly acidic to neutral pH conditions because they can more effectively secrete organic acids to dissolve insoluble phosphate salts. Soluble phosphates can effectively stabilize various heavy metals in fly ash, including lead (Pb) and cadmium (Cd). The dissolved phosphate ions combine with heavy metal ions to form insoluble heavy metal phosphate precipitates. The generated precipitates accumulate in the fly ash cement solidified body and can repair cracks in the cement solidified body caused by aging. The generated precipitates accumulate in the soil, which reduces the bioavailability and mobility of heavy metals and reduces the risk that heavy metals in fly ash may enter the environment through leakage and the like.

[0024] Under landfill geochemical conditions, fly ash solidification and stabilization products will age to varying degrees, resulting in long-term fixation of heavy metals.

[0025] Hydroxyapatite nanoparticles (Ca 10 (PO 4 ) 6 (OH) 2 ), phosphate rock, and superphosphate (Ca(H 2 PO 4 ) 2 ) chelates lead to form stable pyrochloreite (Pb5(PO4)3(Cl / F / OH)), which can precipitate the copper and zinc ions in the fly ash and the lead ions in the fly ash to form a stable lead ion compound. DETAILED DESCRIPTION

[0026] The present invention is further described below in conjunction with specific embodiments. It should be noted that, under the premise of no conflict, the embodiments or technical features described below can be arbitrarily combined to form a new embodiment.

[0027] The synthetic fibers or metal fibers were purchased from Beijing Bailingwei Technology Co., Ltd.

[0028] Sulphoaluminate cement was purchased from Wuhan Jiyesheng Chemical Co., Ltd.

[0029] Sodium tetraphenylborate was provided by Shanghai Aladdin Biochemical Technology Co., Ltd.

[0030] Ca(H 2 PO 4 ) 2 , Ca(H 2 PO4 ) 2 ·CaHPO 4 , Ca 10 (PO 4 ) 6 (OH) 2 , phosphate rock was obtained from Sixin Yunnan Mining Co., Ltd., and the phosphate rock mainly consists of fluorapatite [Ca 5 (PO 4 )3F].

[0031] Purchased from Sinopharm Chemical Reagent Co., Ltd.

[0032] Polymer modified asphalt was purchased from Shandong Yanggu Jiangbei Chemical Co., Ltd.: Polymer modified asphalt is obtained by adding a certain weight proportion of synthetic high molecular polymer (such as SBS, SBR, EVA, etc.) to ordinary base asphalt for physical or chemical modification.

[0033] The matrix asphalt was purchased from Hubei Enxing Biotechnology Co., Ltd.

[0034] The fly ash samples from the incineration of domestic waste were collected from a domestic waste incineration plant in Hunan Province, and the moisture content was 8.253%. After the fly ash was collected, it was dried at 105℃ for 24h, and then preliminarily crushed and ground. After sieving, the fly ash under the sieve was taken as the research object.

[0035] The jaw crusher 150×250 was purchased from Hebi Fengyuan Experimental Instrument Manufacturing Co., Ltd.

[0036] The forced mixer was purchased from Zhengzhou Changli Machinery Manufacturing Co., Ltd.

[0037] Asphalt concrete mixing plant LB-2000 was purchased from Wuxi Taite Road Construction Machinery Co., Ltd.

[0038] Example 1

[0039] This embodiment provides a method for improving the long-term solidification effect of fly ash by a fly ash cement solidification body, comprising the following steps:

[0040] S1. Collect fly ash from the incineration of domestic waste, place the fly ash from the incineration of domestic waste in a hydrothermal reactor for hydrothermal treatment, and after the hydrothermal treatment is completed, collect chlorine generated by decomposition of fly ash chloride during the hydrothermal treatment through a closed pipeline system connected to the hydrothermal reactor. After the chlorine is collected, put the hydrothermal treatment product in the hydrothermal reactor into a stirring device, put sulphoaluminate cement into the stirring device for stirring, add an appropriate amount of sodium tetraphenylborate, and add an appropriate amount of water to stir evenly to form a uniform slurry;

[0041] S2. Select polyester fibers of appropriate length, adjust the viscosity of the slurry, and evenly disperse the polyester fibers in the slurry. An appropriate water-to-binder ratio helps to improve the dispersibility of the polyester fibers in the slurry and avoid sinking of the polyester fibers due to the slurry being too thin. You can start with a medium-viscosity slurry and then gradually adjust it according to the dispersion of the fibers and construction requirements. Select fibers of appropriate length. Fibers that are too long may be more difficult to disperse, while fibers that are too short may not provide sufficient reinforcement effects. Gradually add polyester fibers to the slurry with adjusted viscosity, start mixing with low-speed stirring first to avoid damaging the polyester fibers, and gradually increase the stirring speed to evenly disperse the polyester fibers in the slurry to prevent the fibers from agglomerating. Evenly disperse the polyester fibers in the slurry to obtain a slurry containing polyester fibers.

[0042] S3, after pouring and solidifying the slurry containing polyester fiber, a cement solidified body is obtained, the cement solidified body is crushed by a jaw crusher, and the crushed cement solidified body is put into an asphalt concrete mixing device; the styrene-butadiene-styrene block copolymer modified asphalt and the base asphalt are heated to 160°C respectively, and maintained in this temperature range, so that the styrene-butadiene-styrene block copolymer modified asphalt and the base asphalt change from a semi-solid state to a fluid state, and the heated styrene-butadiene-styrene block copolymer modified asphalt is added to the asphalt concrete mixing device, and stirred evenly, so that the surface of the crushed cement solidified body has a layer of styrene-butadiene-styrene block copolymer modified asphalt, and cooled and solidified, and the crushed cement solidified body A styrene-butadiene-styrene block copolymer modified asphalt layer is formed on the surface. After the styrene-butadiene-styrene block copolymer modified asphalt layer is formed, the cooled and solidified styrene-butadiene-styrene block copolymer modified asphalt layer is heated using a heating device of an asphalt concrete mixing equipment to soften the cooled and solidified styrene-butadiene-styrene block copolymer modified asphalt layer so that the crushed cement solidified body can be separated. The heated matrix asphalt is continuously added into the asphalt concrete mixing equipment, the separated crushed cement solidified body and the heated matrix asphalt are evenly stirred, and a matrix asphalt layer is formed on the styrene-butadiene-styrene block copolymer modified asphalt layer after cooling and solidification to obtain an asphalt-coated cement solidified body.

[0043] Asphalt concrete mixing equipment is a kind of equipment specially used for drying, heating, screening, measuring, adding appropriate amount of filler (stone powder) to sand and gravel, and mixing it with hot asphalt liquid in a certain proportion to form asphalt mixture.

[0044] Fiber-reinforced cement solids can improve the tensile strength, flexural strength and impact toughness of cement solids, reduce the formation and expansion of cracks; show better durability in harsh environments such as freeze-thaw cycles and chemical erosion; can slow down the shrinkage of cement solids, because fibers can bridge tiny cracks, reduce the possibility of them developing into macro cracks, improve the crack resistance of concrete, and reduce micro cracks caused by shrinkage. There is good bonding between the asphalt layer and the cement solid layer, which enhances the bonding strength.

[0045] Sodium tetraphenylborate has relatively good solubility in water. It is slightly hygroscopic and soluble in water, acetone, acetonitrile, and dimethylformamide, but insoluble in benzene and carbon tetrachloride. Sodium tetraphenylborate is easy to decompose in aqueous solution and is generally stable at pH 8-9 or 5-6. This makes sodium tetraphenylborate easier to handle and use in the laboratory, especially when water solubility is required.

[0046] Potassium tetraphenylborate is generally considered to be poorly soluble in water, but it can be dissolved in organic solvents such as acetone, methanol, or dimethyl sulfoxide. This solubility property of potassium tetraphenylborate makes it particularly useful in organic synthesis, especially when reactions need to be carried out in non-aqueous solvents.

[0047] Although the unmodified base asphalt has a certain bonding ability, in order to ensure good bonding between the asphalt layer and the fly ash cement cured layer, polymer-modified asphalt is used as an interface treatment agent.

[0048] In this embodiment, sulphoaluminate cement is a type of cement with better resistance to chloride ion penetration.

[0049] Example 2

[0050] This embodiment provides a method for improving the long-term solidification effect of fly ash by a fly ash cement solidification body, comprising the following steps:

[0051] S1. Collect fly ash from the incineration of domestic waste, place the fly ash from the incineration of domestic waste in a hydrothermal reactor for hydrothermal treatment, and after the hydrothermal treatment is completed, collect chlorine generated by decomposition of fly ash chloride during the hydrothermal treatment through a closed pipeline system connected to the hydrothermal reactor. After the chlorine is collected, put the hydrothermal treatment product in the hydrothermal reactor into a stirring device, put sulphoaluminate cement into the stirring device for stirring, add an appropriate amount of sodium tetraphenylborate, and add an appropriate amount of water to stir evenly to form a uniform slurry;

[0052] S2. Select polyamide fibers of appropriate length, adjust the viscosity of the slurry, and evenly disperse the polyamide fibers in the slurry. An appropriate water-to-binder ratio helps to improve the dispersibility of the polyamide fibers in the slurry and avoid the sinking of the polyamide fibers due to the slurry being too thin. You can start with a medium-viscosity slurry and then gradually adjust it according to the dispersion of the fibers and the construction requirements. Select fibers of appropriate length. Fibers that are too long may be more difficult to disperse, while fibers that are too short may not provide sufficient reinforcement effects. Gradually add polyamide fibers to the slurry with adjusted viscosity, start mixing with low-speed stirring first to avoid damaging the polyamide fibers, and gradually increase the stirring speed to evenly disperse the polyamide fibers in the slurry to prevent the fibers from agglomerating. Evenly disperse the polyamide fibers in the slurry to obtain a slurry containing polyamide fibers.

[0053] S3. After pouring and solidifying the slurry containing polyamide fiber, a cement solidified body is obtained, and the cement solidified body is crushed by a jaw crusher, and the crushed cement solidified body is put into an asphalt concrete mixing device; the ethylene-vinyl acetate copolymer modified asphalt and the base asphalt are heated to 165°C respectively, and maintained in this temperature range to change the ethylene-vinyl acetate copolymer modified asphalt and the base asphalt from a semi-solid state to a fluid state, and the heated ethylene-vinyl acetate copolymer modified asphalt is added to the asphalt concrete mixing device, and stirred evenly, so that the surface of the crushed cement solidified body has a layer of ethylene-vinyl acetate copolymer modified asphalt, and cooled and solidified, and the crushed cement An ethylene-vinyl acetate copolymer modified asphalt layer is formed on the surface of the solidified body. After the ethylene-vinyl acetate copolymer modified asphalt layer is formed, the cooled and solidified ethylene-vinyl acetate copolymer modified asphalt layer is heated by a heating device of an asphalt concrete mixing equipment to soften the cooled and solidified ethylene-vinyl acetate copolymer modified asphalt layer so that the crushed cement solidified body can be separated. The heated base asphalt is continuously added into the asphalt concrete mixing equipment, the separated crushed cement solidified body and the heated base asphalt are evenly mixed, and a base asphalt layer is formed on the ethylene-vinyl acetate copolymer modified asphalt layer after cooling and solidification to obtain an asphalt-coated cement solidified body.

[0054] Asphalt concrete mixing equipment is a kind of equipment specially used for drying, heating, screening, measuring, adding appropriate amount of filler (stone powder) to sand and gravel, and mixing it with hot asphalt liquid in a certain proportion to form asphalt mixture.

[0055] Fiber-reinforced cement solids can improve the tensile strength, flexural strength and impact toughness of cement solids, reduce the formation and expansion of cracks; show better durability in harsh environments such as freeze-thaw cycles and chemical erosion; can slow down the shrinkage of cement solids, because fibers can bridge tiny cracks, reduce the possibility of them developing into macro cracks, improve the crack resistance of concrete, and reduce micro cracks caused by shrinkage. There is good bonding between the asphalt layer and the cement solid layer, which enhances the bonding strength.

[0056] Example 3

[0057] This embodiment provides a method for improving the long-term solidification effect of fly ash by a fly ash cement solidification body, comprising the following steps:

[0058] S1. Collect fly ash from the incineration of domestic waste, place the fly ash from the incineration of domestic waste in a hydrothermal reactor for hydrothermal treatment, and after the hydrothermal treatment is completed, collect chlorine generated by decomposition of fly ash chloride during the hydrothermal treatment through a closed pipeline system connected to the hydrothermal reactor. After the chlorine is collected, put the hydrothermal treatment product in the hydrothermal reactor into a stirring device, put sulphoaluminate cement into the stirring device for stirring, add an appropriate amount of sodium tetraphenylborate, and add an appropriate amount of water to stir evenly to form a uniform slurry;

[0059] S2. Select polyacrylonitrile fibers of appropriate length, adjust the viscosity of the slurry, and make the polyacrylonitrile fibers evenly dispersed in the slurry. An appropriate water-to-binder ratio helps to improve the dispersibility of the polyacrylonitrile fibers in the slurry and avoid the sinking of the polyacrylonitrile fibers due to the slurry being too thin. You can start with a medium-viscosity slurry and then gradually adjust it according to the dispersion of the fibers and the construction requirements. Select fibers of appropriate length. Fibers that are too long may be more difficult to disperse, while fibers that are too short may not provide sufficient reinforcement effects. Gradually add polyacrylonitrile fibers to the slurry with adjusted viscosity, start mixing with low-speed stirring first to avoid damaging the polyacrylonitrile fibers, and gradually increase the stirring speed to make the polyacrylonitrile fibers evenly dispersed in the slurry to prevent the fibers from agglomerating. Make the polyacrylonitrile fibers evenly dispersed in the slurry to obtain a slurry containing polyacrylonitrile fibers.

[0060] S3, after pouring and solidifying the slurry containing polyacrylonitrile fiber, a cement solidified body is obtained, the cement solidified body is crushed by a jaw crusher, and the crushed cement solidified body is put into an asphalt concrete mixing device; the styrene-butadiene rubber modified asphalt and the base asphalt are heated to 180°C respectively, and maintained in this temperature range, so that the styrene-butadiene rubber modified asphalt and the base asphalt change from a semi-solid state to a fluid state, and the heated styrene-butadiene rubber modified asphalt is added to the asphalt concrete mixing device, and stirred evenly, so that the surface of the crushed cement solidified body has a layer of styrene-butadiene rubber modified asphalt, and cooled and solidified, and crushed. A styrene-butadiene rubber modified asphalt layer is formed on the surface of the cement solidified body. After the styrene-butadiene rubber modified asphalt layer is formed, the cooled and solidified styrene-butadiene rubber modified asphalt layer is heated by a heating device of an asphalt concrete mixing equipment to soften the cooled and solidified styrene-butadiene rubber modified asphalt layer so that the crushed cement solidified body can be separated. The heated matrix asphalt is continuously added into the asphalt concrete mixing equipment, the separated crushed cement solidified body and the heated matrix asphalt are evenly mixed, and a matrix asphalt layer is formed on the styrene-butadiene rubber modified asphalt layer after cooling and solidification to obtain an asphalt-coated cement solidified body.

[0061] Asphalt concrete mixing equipment is a kind of equipment specially used for drying, heating, screening, measuring, adding appropriate amount of filler (stone powder) to sand and gravel, and mixing it with hot asphalt liquid in a certain proportion to form asphalt mixture.

[0062] Fiber-reinforced cement solids can improve the tensile strength, flexural strength and impact toughness of cement solids, reduce the formation and expansion of cracks; show better durability in harsh environments such as freeze-thaw cycles and chemical erosion; can slow down the shrinkage of cement solids, because fibers can bridge tiny cracks, reduce the possibility of them developing into macro cracks, improve the crack resistance of concrete, and reduce micro cracks caused by shrinkage. There is good bonding between the asphalt layer and the cement solid layer, which enhances the bonding strength.

[0063] Example 4

[0064] This embodiment provides a method for improving the long-term solidification effect of fly ash by a fly ash cement solidification body, comprising the following steps:

[0065] S1. Collect fly ash from the incineration of domestic waste, place the fly ash from the incineration of domestic waste in a hydrothermal reactor for hydrothermal treatment, and after the hydrothermal treatment is completed, collect chlorine generated by decomposition of fly ash chloride during the hydrothermal treatment through a closed pipeline system connected to the hydrothermal reactor. After the chlorine is collected, put the hydrothermal treatment product in the hydrothermal reactor into a stirring device, put sulphoaluminate cement into the stirring device for stirring, add an appropriate amount of sodium tetraphenylborate, and add an appropriate amount of water to stir evenly to form a uniform slurry;

[0066] S2. Select stainless steel fibers of appropriate length, adjust the viscosity of the slurry, and evenly disperse the stainless steel fibers in the slurry. An appropriate water-to-binder ratio helps to improve the dispersibility of the stainless steel fibers in the slurry and avoid the sinking of the stainless steel fibers due to the slurry being too thin. You can start with a medium-viscosity slurry and then gradually adjust it according to the dispersion of the fibers and the construction requirements. Select fibers of appropriate length. Fibers that are too long may be more difficult to disperse, while fibers that are too short may not provide sufficient reinforcement effects. Gradually add stainless steel fibers to the slurry with adjusted viscosity, start mixing with low-speed stirring first to avoid damage to the stainless steel fibers, and gradually increase the stirring speed to evenly disperse the stainless steel fibers in the slurry to prevent the fibers from agglomerating. Evenly disperse the stainless steel fibers in the slurry to obtain a slurry containing stainless steel fibers.

[0067] S3. After pouring and solidifying the slurry containing stainless steel fibers, a cement solidified body is obtained, and the cement solidified body is crushed by a jaw crusher. The crushed cement solidified body is put into an asphalt concrete mixing device; the polyethylene modified asphalt and the base asphalt are heated to 185°C respectively and maintained in this temperature range so that the polyethylene modified asphalt and the base asphalt change from a semi-solid state to a fluid state, and the heated polyethylene modified asphalt is added to the asphalt concrete mixing device and stirred evenly so that the surface of the crushed cement solidified body is provided with a layer of polyethylene modified asphalt, and the crushed cement solidified body is cooled and solidified to form a polyethylene modified asphalt layer on the surface of the crushed cement solidified body. After the polyethylene modified asphalt layer is formed, the cooled and solidified polyethylene modified asphalt layer is heated by a heating device of the asphalt concrete mixing device to soften the cooled and solidified polyethylene modified asphalt layer so that the crushed cement solidified body can be separated, and the heated base asphalt is continuously added to the asphalt concrete mixing device, and the separated crushed cement solidified body and the heated base asphalt are stirred evenly, and a base asphalt layer is formed on the polyethylene modified asphalt layer after cooling and solidification to obtain an asphalt-coated cement solidified body.

[0068] Asphalt concrete mixing equipment is a kind of equipment specially used for drying, heating, screening, measuring, adding appropriate amount of filler (stone powder) to sand and gravel, and mixing it with hot asphalt liquid in a certain proportion to form asphalt mixture.

[0069] Fiber-reinforced cement solids can improve the tensile strength, flexural strength and impact toughness of cement solids, reduce the formation and expansion of cracks; show better durability in harsh environments such as freeze-thaw cycles and chemical erosion; can slow down the shrinkage of cement solids, because fibers can bridge tiny cracks, reduce the possibility of them developing into macro cracks, improve the crack resistance of concrete, and reduce micro cracks caused by shrinkage. There is good bonding between the asphalt layer and the cement solid layer, which enhances the bonding strength.

[0070] Example 5

[0071] This embodiment provides a method for improving the long-term solidification effect of fly ash by a fly ash cement solidification body, comprising the following steps:

[0072] S1. Collect fly ash from the incineration of domestic waste, place the fly ash from the incineration of domestic waste in a hydrothermal reactor for hydrothermal treatment, and after the hydrothermal treatment is completed, collect chlorine generated by decomposition of fly ash chloride during the hydrothermal treatment through a closed pipeline system connected to the hydrothermal reactor. After the chlorine is collected, put the hydrothermal treatment product in the hydrothermal reactor into a stirring device, put sulphoaluminate cement into the stirring device for stirring, add an appropriate amount of sodium tetraphenylborate, and add an appropriate amount of water to stir evenly to form a uniform slurry;

[0073] S2. Select copper fibers of appropriate length, adjust the viscosity of the slurry, and evenly disperse the copper fibers in the slurry. An appropriate water-to-binder ratio helps to improve the dispersibility of synthetic fibers or copper fibers in the slurry and avoid sinking of copper fibers due to excessive dilution of the slurry. You can start with a medium-viscosity slurry and then gradually adjust it according to the dispersion of the fibers and construction requirements. Select fibers of appropriate length. Fibers that are too long may be more difficult to disperse, while fibers that are too short may not provide sufficient reinforcement effects. Gradually add copper fibers to the slurry with adjusted viscosity, start mixing with low-speed stirring first to avoid damage to the copper fibers, and gradually increase the stirring speed to evenly disperse the copper fibers in the slurry to prevent fiber agglomeration. Evenly disperse the copper fibers in the slurry to obtain a slurry containing copper fibers.

[0074] S3, after pouring and solidifying the slurry containing copper fibers, a cement solidified body is obtained, the cement solidified body is crushed by a jaw crusher, and the crushed cement solidified body is put into an asphalt concrete mixing device; the styrene-butadiene-styrene block copolymer modified asphalt and the base asphalt are heated to 160°C respectively, and maintained in this temperature range, so that the styrene-butadiene-styrene block copolymer modified asphalt and the base asphalt are changed from a semi-solid state to a fluid state, and the heated styrene-butadiene-styrene block copolymer modified asphalt is added to the asphalt concrete mixing device, and stirred evenly, so that the surface of the crushed cement solidified body has a layer of styrene-butadiene-styrene block copolymer modified asphalt, and cooled and solidified, and the crushed cement solidified body A styrene-butadiene-styrene block copolymer modified asphalt layer is formed on the surface. After the styrene-butadiene-styrene block copolymer modified asphalt layer is formed, the cooled and solidified styrene-butadiene-styrene block copolymer modified asphalt layer is heated using a heating device of an asphalt concrete mixing device to soften the cooled and solidified styrene-butadiene-styrene block copolymer modified asphalt layer so that the crushed cement solidified body can be separated. The heated matrix asphalt is continuously added into the asphalt concrete mixing device, the separated crushed cement solidified body and the heated matrix asphalt are uniformly stirred, and a matrix asphalt layer is formed on the styrene-butadiene-styrene block copolymer modified asphalt layer after cooling and solidification, thereby obtaining an asphalt-coated cement solidified body;

[0075] S4, the insoluble phosphate Ca(H 2 PO 4 ) 2 After mixing with biochar, the insoluble phosphate Ca(H 2 PO 4 ) 2 and biochar, in a specific implementation, strips or grooves are formed in the soil to transfer the insoluble phosphate Ca(H 2 PO 4 ) 2 After the biochar is applied, the soil is covered and the phosphate-solubilizing bacteria microbial preparation is applied to the soil of the domestic waste landfill. In the specific implementation, the microbial preparation is dissolved in water through an irrigation system, and then evenly sprayed or dripped into the soil and then the asphalt-coated cement solid body is buried in the domestic waste landfill.

[0076] The sparingly soluble phosphate salt can also be Ca(H 2 PO 4 ) 2 ·CaHPO 4 , Ca 10 (PO 4 ) 6 (OH) 2 .

[0077] Comparative Example 1

[0078] This comparative example provides a method for improving the long-term solidification effect of fly ash by fly ash cement solidification body, comprising the following steps:

[0079] S1. Collect fly ash from the incineration of domestic waste, place the fly ash from the incineration of domestic waste in a hydrothermal reactor for hydrothermal treatment, and after the hydrothermal treatment is completed, collect chlorine generated by decomposition of fly ash chloride during the hydrothermal treatment through a closed pipeline system connected to the hydrothermal reactor. After the chlorine is collected, put the hydrothermal treatment product in the hydrothermal reactor into a stirring device, put sulphoaluminate cement into the stirring device for stirring, add an appropriate amount of sodium tetraphenylborate, and add an appropriate amount of water to stir evenly to form a uniform slurry;

[0080] S2. Select polyester fibers of appropriate length, adjust the viscosity of the slurry, and evenly disperse the polyester fibers in the slurry. An appropriate water-to-binder ratio helps to improve the dispersibility of the polyester fibers in the slurry and avoid sinking of the polyester fibers due to the slurry being too thin. You can start with a medium-viscosity slurry and then gradually adjust it according to the dispersion of the fibers and construction requirements. Select fibers of appropriate length. Fibers that are too long may be more difficult to disperse, while fibers that are too short may not provide sufficient reinforcement effects. Gradually add polyester fibers to the slurry with adjusted viscosity, start mixing with low-speed stirring first to avoid damaging the polyester fibers, and gradually increase the stirring speed to evenly disperse the polyester fibers in the slurry to prevent the fibers from agglomerating. Evenly disperse the polyester fibers in the slurry to obtain a slurry containing polyester fibers.

[0081] S3, pouring and solidifying the slurry containing polyester fibers to obtain a cement solidified body.

[0082] Comparative Example 2

[0083] This comparative example provides a method for improving the long-term solidification effect of fly ash by fly ash cement solidification body, comprising the following steps:

[0084] S1. Collect fly ash from the incineration of domestic waste, put the fly ash from the incineration of domestic waste into a stirring device, put sulphoaluminate cement into the stirring device for stirring, and add an appropriate amount of water to stir evenly to form a uniform slurry;

[0085] S2. Select polyester fibers of appropriate length, adjust the viscosity of the slurry, and evenly disperse the polyester fibers in the slurry. An appropriate water-to-binder ratio helps to improve the dispersibility of the polyester fibers in the slurry and avoid sinking of the polyester fibers due to the slurry being too thin. You can start with a medium-viscosity slurry and then gradually adjust it according to the dispersion of the fibers and construction requirements. Select fibers of appropriate length. Fibers that are too long may be more difficult to disperse, while fibers that are too short may not provide sufficient reinforcement effects. Gradually add polyester fibers to the slurry with adjusted viscosity, start mixing with low-speed stirring first to avoid damaging the polyester fibers, and gradually increase the stirring speed to evenly disperse the polyester fibers in the slurry to prevent the fibers from agglomerating. Evenly disperse the polyester fibers in the slurry to obtain a slurry containing polyester fibers.

[0086] S3, pouring and solidifying the slurry containing polyester fibers to obtain a cement solidified body.

[0087] Experimental example

[0088] Artificial accelerated aging experiment in carbon dioxide incubator

[0089] The asphalt-coated cement solidified body provided in Example 1-4 and the asphalt-coated cement solidified body provided in Comparative Example 1-2 were placed in a carbon dioxide incubator respectively. A 3L water tray containing 3L sterile pure water was placed in the carbon dioxide incubator. The temperature was 37 degrees, and the water evaporated naturally to make the humidity in the box reach 95%. The air valve was adjusted to make the carbon dioxide concentration in the carbon dioxide incubator reach 50%. The experiment was carried out for one month. After one month, the bodies were taken out for observation and immersed in deionized water for 3 hours. The concentration of heavy metals in the water was detected by atomic absorption spectrometer. The results are shown in Table 1.

[0090] The test results of heavy metal ion concentrations in water of Examples 1-4 and Comparative Examples 1-2 are shown in Table 1.

[0091] Table 1

[0092]

[0093]

[0094]

[0095] The results in Table 1 show that no heavy metal ions were detected in the water of Examples 1-4, the heavy metal ion concentration in the water of Comparative Example 2 was significantly higher than that in Comparative Example 1, and the heavy metal ion concentration in the water of Comparative Examples 1 and 2 was significantly higher than that of Examples 1-4.

[0096] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.

Claims

1. A method for improving the long-term solidification effect of fly ash by fly ash cement solidification, characterized in that: The following steps are involved: S1. Collect fly ash from incineration of domestic waste, place the fly ash in a hydrothermal reactor for hydrothermal treatment, and after the hydrothermal treatment, collect chlorine generated by decomposition of fly ash chloride during the hydrothermal treatment through a closed pipeline system connected to the hydrothermal reactor. After the chlorine is collected, put the hydrothermal treatment product in the hydrothermal reactor into a stirring device, put cement into the stirring device for stirring, and stir the added water evenly to form a uniform slurry; S2, selecting synthetic fibers or metal fibers of appropriate length, adjusting the viscosity of the slurry so that the synthetic fibers or metal fibers are evenly dispersed in the slurry, gradually adding the synthetic fibers or metal fibers to the slurry with adjusted viscosity, first stirring at a low speed to start mixing to avoid damaging the synthetic fibers or metal fibers, and gradually increasing the stirring speed so that the synthetic fibers or metal fibers are evenly dispersed in the slurry, thereby obtaining a slurry containing synthetic fibers or metal fibers; S3, after pouring and solidifying the slurry containing synthetic fibers or metal fibers, a cement solidified body is obtained, the cement solidified body is crushed by a jaw crusher, and the crushed cement solidified body is put into an asphalt concrete mixing device; the polymer modified asphalt and the base asphalt are heated to 160°C-185°C respectively, and maintained in this temperature range, the heated polymer modified asphalt is added to the asphalt concrete mixing device, and stirred evenly, so that the surface of the crushed cement solidified body is provided with a layer of the polymer modified asphalt, and cooled and solidified, a polymer modified asphalt layer is formed on the surface of the crushed cement solidified body, after the polymer modified asphalt layer is formed, the cooled and solidified polymer modified asphalt layer is heated by a heating device of the asphalt concrete mixing device, so that the cooled and solidified polymer modified asphalt layer is softened, so that the crushed cement solidified body can be separated, and the heated base asphalt is continuously added to the asphalt concrete mixing device, and the separated crushed cement solidified body and the heated base asphalt are stirred evenly, and after cooling and solidification, a base asphalt layer is formed on the polymer modified asphalt layer, so as to obtain an asphalt-coated cement solidified body; After obtaining the asphalt-coated cement solid body in step S3, the insoluble phosphate salt and biochar are mixed, and the mixture of the insoluble phosphate salt and the biochar is buried in the surface layer of the soil of the domestic waste landfill, and the phosphate-solubilizing bacteria microbial preparation is applied to the soil of the domestic waste landfill, and then the asphalt-coated cement solid body is buried in the domestic waste landfill.

2. A method for improving the long-term solidification effect of fly ash by fly ash cement solidification body according to claim 1, characterized in that: In step S2, a forced mixer is used to stir the synthetic fibers or metal fibers.

3. A method for improving the long-term solidification effect of fly ash by fly ash cement solidification body according to claim 1, characterized in that: In step S1, in the stirring device, the fly ash, the cement and the water are added in a weight ratio of 1:0.2:

3.

4. A method for improving the long-term solidification effect of fly ash by fly ash cement solidification body according to claim 2, characterized in that: In step S2, the synthetic fiber is one of polyester fiber, polyamide fiber, polyacrylonitrile fiber, polyvinyl formal fiber, polyvinyl chloride fiber, and polyurethane elastic fiber; the metal fiber is one of stainless steel fiber, copper fiber, nickel fiber, and aluminum fiber.

5. A method for improving the long-term solidification effect of fly ash by fly ash cement solidification body according to claim 1, characterized in that: In step S1, the cement is sulphoaluminate cement.

6. A method for improving the long-term solidification effect of fly ash by fly ash cement solidification body according to claim 1, characterized in that: In step S3, the jaw crusher is one of a simple swing jaw crusher, a compound swing jaw crusher or a hydraulic jaw crusher.

7. A method for improving the long-term solidification effect of fly ash by fly ash cement solidification body according to claim 1, characterized in that: In step S3, the polymer modified asphalt is obtained by modifying the base asphalt with one of the following polymers: styrene-butadiene-styrene block copolymer, styrene-butadiene rubber, ethylene-vinyl acetate copolymer, polyethylene, and polyurethane.

8. A method for improving the long-term solidification effect of fly ash by fly ash cement solidification body according to claim 1, characterized in that: In step S1, the cement is put into the stirring device for stirring, and the added water is stirred evenly. In this step, sodium tetraphenylborate is also added and stirred evenly.

9. A method for improving the long-term solidification effect of fly ash by fly ash cement solidification body according to claim 1, characterized in that: The sparingly soluble phosphate salts are Ca(H2PO4)2, Ca(H2PO4)2•CaHPO4, Ca 10 One of (PO4)6(OH)2.

Citation Information

Patent Citations

  • Curing and stabilizing treatment method for garbage incineration fly ash

    CN105964652A

  • Continuous fly ash dioxin hydrothermal degradation and heavy metal solidification system and method

    CN116851421A

  • Treatment equipment for hazardous waste incineration residues

    CN219616362U

  • Low noise asphaltconcrete with high durability

    KR102199284B1